Signal peptide sequence analysis of selected protein sequences from Cryptosporidium parvum - Barudin, Mohd Aiman; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (Asian Network for Scientific Information, 2018)
Background and Objective: Studies on signal peptides remain little and lacking to Cryptosporidium. This study represents the first attempt to investigate selected putative protein sequences of Cryptosporidium parvum in its established genome database for signal peptide. Methods: Prediction analysis of protein sequences and identification of signal peptides on this parasite were analysed by SignalP 4.1 server. A total of 100 protein sequences were randomly selected and analysed, of which 6 (6%) corresponded to be predicted as signal peptide sequences. Results: Based on the comparison of sequences with database protein sequences in GenBank NCBI, almost all protein sequences were highly conserved with other protein sequences from different species of Cryptosporidium. Considering the secretory proteins in Cryptosporidium, several virulence protein sequences of this parasite may also show presence of N-terminal signal peptide or not. Conclusions: Hence, further studies need to be carried out for identification of N-terminal signal peptide function in Cryptosporidium for facilitating its virulence and pathogenesis pathway.